Realizing Present and Future Promise of DIY Biology and Medicine through a Trust Architecture - Rasmussen, Lisa M. (The Hastings Center report, 2020)
The speed and scale of the COVID-19 pandemic has highlighted the limits of current health systems and the potential promise of non-establishment research such as “DIY” research. We consider one example of how DIY research is responding to the pandemic, discuss the challenges faced by DIY research more generally, and suggest that a “trust architecture” should be developed now to contribute to successful future DIY efforts.